Pharmacological characterization of the behavioural syndrome induced by the NK-3 tachykinin agonist senktide in rodents: evidence for mediation by endogenous 5-HT. - Stoessl, A; Dourish, C; Iversen, S (1990)
The effects of various manipulations of brain 5-HT mechanisms on the behavioural responses induced by the selective NK-3 tachykinin agonist senktide in rodents were assessed. Senktide elicited wet dog shakes in the rat which were attenuated by the 5-HT1C/2 antagonist mianserin and the selective 5-HT2 antagonist altanserin. Senktide-induced forepaw treading was stereospecifically attenuated by the 5-HT1A + B antagonist (-)-alprenolol. Senktide also elicited chewing mouth movements and yawning, which were unaffected by mianserin, altanserin, (+)- or (-)-alprenolol, or the selective 5-HT3 antagonist ICS 205-930, but attenuated by the muscarinic antagonist scopolamine. Penile grooming elicited by senktide was attenuated by mianserin, but was unaffected by the other antagonists. Senktide-induced wet dog shakes were enhanced by the 5-HT reuptake inhibitors citalopram and fluoxetine, suppressed by the monoamine oxidase (MAO)-B inhibitor pargyline, but unaffected by the MAO-A inhibitor clorgyline. Forepaw treading was potentiated by citalopram and clorgyline, but not significantly altered by fluoxetine or pargyline. Depletion of 5-HT by p-chlorophenylalanine (PCPA) in the rat attenuated senktide-induced wet dog shakes and forepaw treading. Neither PCPA nor 5,7-dihydroxytryptamine affected senktide-induced behaviours in the mouse, but the degree of brain 5-HT depletion caused by these treatments in mice was relatively small. These findings indicate that stimulation of NK-3 tachykinin receptors by senktide results in a complex behavioural syndrome which is mediated by multiple 5-HT receptors, and dependent upon intact stores of endogenous 5-HT. Independent stimulation of brain cholinergic mechanisms by senktide is also confirmed.